Remote ischemic preconditioning can extend the tolerance to extended drug-coated balloon inflation time by reducing myocardial damage during percutaneous coronary intervention. (15th April 2022) - Zhao, Zhenzhou; Shi, Qingbo; Guo, Quan; Peng, Liang; Li, Xuejie; Rao, Lixin; Li, Muwei
Abstract: Background: Remote ischemic preconditioning (RIPC) alleviates myocardial ischemia-reperfusion injury (IRI) that occurs during percutaneous coronary intervention (PCI) and increases the myocardial tolerance to ischemia and hypoxia. Prolonged inflation time of drug-coated balloons (DCBs) can improve the treatment effects of PCI and the long-term prognosis of patients. This study investigated whether preoperative RIPC improves the tolerance to extended DCB inflation time. Methods and results: Overall, 345 patients with coronary artery disease (CAD) were enrolled; 90, 96, 83, and 76 of these were randomized into the upper limb RIPC, lower limb RIPC, upper limb control, and lower limb control groups, respectively. Their baseline data were collected. Data on cardiac markers were analyzed. The DCB inflation time was recorded. The baseline data and cardiac marker levels before operation did not differ between RIPC and control groups. The post-PCI high-sensitivity troponin-T levels were lower in the RIPC groups (35.81 ± 14.02 and 34.65 ± 14.86 pg/mL) than in the control groups (41.63 ± 18.31 and 42.24 ± 14.38 pg/mL) (P = 0.001). The DCB inflation tolerance time was higher in the lower limb RIPC group (120 s [120, 120]) than in the upper limb RIPC group (120 s [110, 120]), and was the lowest in the upper limb control (100 s [90, 120]) and the lower limb control (100 s [90, 115]) groups (P < 0.001). Conclusions: RIPC reduces the level of myocardial damage that occurs during PCI and prolongs tolerance to increased DCB inflation time. The larger the ischemic area in RIPC, the better the improvement in the tolerance to extended DCB inflation time. Highlights: This study suggests that short-term preoperative RIPC can increase the DCB inflation tolerance time. The short-term application of RIPC before operation can reduce myocardial injury secondary to PCI. The larger the ischemic area of RIPC, the more significant the improvement of DCB tolerance time.